Utility of uterine artery Doppler and pulsatility index at 11-14 weeks of normal pregnancy in prediction of preeclampsia in third trimester - Jyoti Bindal; Niketa Chugh (International Journal of Medical Research and Review, 2016)
Introduction: Preeclampsia affects 5-8% of women in pregnancy and leading cause of maternal mortality. The present study was done to predict the development of preeclampsia in patients with uterine artery pulsatility index (PI) >1.71 and the presence of diastolic notch at 11-14 weeks of gestation belonging to low risk population.Methods: Women attending routine antenatal care were offered an early transvaginal ultrasound scan between 11-14 weeks including uterine artery doppler assessment. Mean PI and presence or absence of bilateral early diastolic notch was also noted. All patients were followed up to term for the development of preeclampsia.Results: Out of 100 patients, 22% developed preeclampsia of which 15 (68.18%) cases showed the presence of diastolic notch and 12 (54.54%) cases had PI >1.71 (p<0.05). A Total of 12% of patients showed presence of both diastolic notch and PI of >1.71 (p<0.05). Out of 37 nulliparous patients 13 (35.13%) developed preeclampsia, 8 (13.79%) out of 58 primiparous and 1 (20%) out of 5 multipara developed preeclampsia (p<0.05). All 11 patients with systolic blood pressure >140mm of Hg at 11-14 weeks of gestation developed preeclampsia (p<0.05).Conclusion: Presence of diastolic notch and PI of >1.71 in uterine artery colour doppler at 11-14 weeks of gestation serves as a good predictor of preeclampsia at term, in pregnancies with no other associated risk factors.